TI_GERICHTE 11.2009.192 vom 19. November 2009 , Misure provvisionali in pendenza di divorzio: blocco di un conto bancario - TI Tribunale d'appello (2009)
Misure provvisionali in pendenza di divorzio: blocco di un conto bancario